Pharmaceutico-analytical study of abhraka bhasma: biosynthesized Traditional mica nanoparticles using Classical and modern methods. - DR. NIKHIL CHAUDHARI; DR. NINAD SATHE (International Journal of Pharma and Bio Sciences, 2018)
In present study krishna-vajra-abhraka-bhasma was prepared using different methods. Raw abhraka was processed for shodhana, dhanyabhraka nirmana, mardana, marana, putapaka. Dhanyabhraka was divided into three samples: 1st and 2nd sample subjected to puta (incineration) using gajaputa according to the classical reference and 3rd sample to EMF according to recent advanced method. All the samples of abhraka bhasma qualified all bhasma pariksha including amla pariksha after the 10thputa. SEM analysis at resolution 100nm and magnification 75000× showed particle size of sample 1(gajaputa), sample 2(gajaputa) and sample 3(EMF) of abhraka bhasma reached 120, 20.6 and 60 nm respectively. Considering all the above parameters it can be concluded that sample 2 of abhraka bhasma prepared classically giving mardana for 5-8 hours and 300-350 cow-dung-cakes per gajaputa reached more reduced size and stands better in quality than that of other samples of abhraka bhasma. Also, sample 3(EMF) prepared contemporarily can yield better results if levigated for 4-5 hours and incinerated at a temperature of 700oC. The manufacturing method of abhraka bhasma is in tune with nanotechnology of contemporary era which may cover scientific validation of today.